Peran Grit terhadap Prokrastinasi Akademik pada Mahasiswa Perguruan Tinggi Swasta di Jakarta - Anggerahma, Shelma; Suryadi, Denrich (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to examine the role of grit in academic procrastination among students at private universities in Jakarta. Grit, as defined by Duckworth (2016, in Utanto & Satiningsih, 2022), is the combination of passion and perseverance to achieve long-term goals. Meanwhile, academic procrastination is defined by Balkis (2013, in Sartika & Nirbita, 2021) as the irrational tendency to delay completing academic tasks. The study employed a quantitative method with a correlational design to investigate the relationship between the two variables. Data were collected from 352 students at private universities in Jakarta through a questionnaire. Academic procrastination was measured using an instrument based on Ferrari’s (1995) theory, while grit was measured using the Short Grit Scale (Grit-S) developed by Duckworth and Quinn. This research used a correlational study with a quantitative approach, including two variables: grit as the independent variable and academic procrastination as the dependent variable. Spearman's correlation analysis was employed, and the results showed an r-value of -0.549 and p = 0.000 < 0.05. This indicates that the higher the level of grit a student possesses, the lower their level of academic procrastination. These findings suggest that characteristics such as perseverance and consistency in pursuing goals can help students reduce their tendency to procrastinate on academic tasks. The study provides significant implications for the development of intervention programs in universities aimed at enhancing students’ grit, helping them better manage their time, and improving academic performance. Additionally, the findings contribute to the literature on educational psychology, particularly in the context of private university students in Jakarta.